Digital literacy of library and information science postgraduates and ubiquitous learning in state owned universities, south-south, Nigeria - Onyema Nsirim; Oluchi Okeke (Folia Toruniensia)
The study investigated digital literacy of library and information science postgraduate students and ubiquitous learning in state universities in south-South, Nigeria. Four (4) objectives, four research questions, and four hypotheses guided the study. The hypotheses were tested at 0.05 level of significance. The study adopted a correlational design and the population was 221 comprising library and information science postgraduate students from eight (8) state universities in South-South, Nigeria. The census sampling technique was used to select the entire population of 221 which represents the sample size. Instrument titled “Digital Literacy of Library and Information Science Postgraduate Students and Ubiquitous Learning Questionnaire” (DLLISPSULQ) was used for data collection. The reliability of the instrument was established through test-retest methods and was determined using Cronbach Alpha method which yielded reliability coefficient of 0.89. The study was analyzed using mean and standard deviation for research questions and Pearson Product Moment Correlation for hypotheses. It was revealed that there was a significant relationship between digital literacy of LIS postgraduate students and ubiquitous learning in state universities in South-South, Nigeria. It was recommended that Library and Information Science schools in South-South, Nigeria should as a matter of policy direct all LIS educators to adopt the use of ubiquitous technologies in teaching to enhance the adoption of ubiquitous learning by Postgraduate students.